Ranula: a narrative review - Swain, Santosh Kumar; Dubey, Debasmita (International Journal of Research in Medical Sciences, 2022)
A ranula is a pseudocystic lesion of the sublingual salivary gland, found in the floor of the mouth. Ranula is classified into types such as simple and plunging type. Plunging ranula arises when a simple ranula extends beyond the floor of the mouth into the neck. A simple ranula is seen above the level of the mylohyoid muscle and is often the result of sublingual gland duct obstruction. A plunging ranula refers to a pseudocyst that develops with salivary duct rupture and is seen below the level of the mylohyoid muscle. Diagnosis of the ranula is difficult even with modern imaging techniques as this mimic to other neck lesions. The correct diagnosis of the ranula is essential for the most effective treatment. The treatment modalities of the ranula currently include marsupialization, excision of the ranula with or without excision of the sublingual gland, cryosurgery, laser excision, sclerotherapy, fenestrations, and continuous pressure. The treatment of the ranula includes complete excision and marsupialization is not a sufficient treatment. Misdiagnosis of a plunging ranula leads to unnecessary and extensive surgery. This review article discussed the epidemiology, etiopathogenesis, clinical features, diagnosis, and current treatment of ranula.